Progress on advanced & smart materials in engineering and mathematics - Mohd Rosli, Zulkifli (Penerbit UTeM Press, 2023)
The Progress on Advanced & Smart Materials in Engineering and Mathematics book, edited by the Smart Materials Research Group, covers multi-disciplinary topics including engineering materials, manufacturing processes, product design, mathematical simulation, and materials analysis. The book is a collaboration between researchers from the Smart Materials Group, academic staff, and students at Fakulti Kejuruteraan Pembuatan and Fakulti Teknologi Kejuruteraan. The Ministry of Higher Education and Universiti Teknikal Malaysia Melaka (UTeM) are also commended for their support.